1993
DOI: 10.1128/jcm.31.2.323-328.1993
|View full text |Cite
|
Sign up to set email alerts
|

Detection of parvovirus B19 in donated blood: a model system for screening by polymerase chain reaction

Abstract: A highly sensitive and rapid method for routinely screening large numbers of donated blood units for parvovirus B19 by the polymerase chain reaction (PCR) was developed. Over a 3-month trial period in Edinburgh, B19 DNA was detected in 6 of 20,000 consecutive units of blood (0.03%), in concentrations ranging from 2.4 x 104 to 5 x 1010 copies of viral DNA per ml. Seroconversion for B19-specific immunoglobulin M and immunoglobulin G and disappearance of circulating B19 DNA occurred in the interval between donati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
66
0

Year Published

1994
1994
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 172 publications
(69 citation statements)
references
References 40 publications
3
66
0
Order By: Relevance
“…The frequency of B19 viremia in voluntary blood donors has been estimated to range from 1:260 to 1:50,000 and to depend on both the sensitivity of the screening method and the season. [24][25][26] Here we report results from screening blood donors over a period of more than 4 years with a sensitive real-time NAT method. The mean frequency of DNA-positive blood donors was 274 per 100,000 donations, which was within the range previously reported.…”
Section: Discussionmentioning
confidence: 99%
“…The frequency of B19 viremia in voluntary blood donors has been estimated to range from 1:260 to 1:50,000 and to depend on both the sensitivity of the screening method and the season. [24][25][26] Here we report results from screening blood donors over a period of more than 4 years with a sensitive real-time NAT method. The mean frequency of DNA-positive blood donors was 274 per 100,000 donations, which was within the range previously reported.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, McOmish et al Numbers in parentheses represcnt the number of ELISA-positi\e samples in each age group. [30] reported that in screening donated blood units in the Edinburgh area for B19 viremia by the polymerase chain reaction, the incidence over a 3-month trial period among healthy blood donors was approximately 113,300, in concentrations ranging from 2 . 4~1 0~ to 5x10"' copies of HI9 DNA/ml.…”
Section: Discussionmentioning
confidence: 99%
“…Inactivation of B19 in IVIG preparations by liquid heat treatment at 60°C for 10 h (used for commercial production of IVIG) was demonstrated (Yunoki et al, 2005). However, dry heat treatment at 60°C for 10 h reduces but does not always inactivate B19 DNA in factor VIII concentrates (McOmish et al, 1993).…”
Section: Virus Inactivation and Removalmentioning
confidence: 99%